Pemanfaatan Kebudayaan Powele dalam Pembelajaran IPS - Ismail Ismail; Moh. Imron Rosidi (Journal on Education, 2023)
Muna is one of the regencies in Southeast Sulawesi Province which has a diversity of arts, culture and tribes. One of the traditional art forms that has now become the identity of Muna Regency is the Powele Traditional Silat. Powele Traditional Silat is a traditional martial art inherited from the ancestors of Muna People. Powele Traditional Silat is very interesting and functions as a medium of education without losing its cultural values. This research method uses literature study. The results showed that the Powele Traditional Silat is a cultural embodiment with noble values that must be upheld and preserved. In carrying out the Powele Traditional Silat tradition, there are character values such as solidarity, leadership, patience and peace that need to be instilled in students. Utilization of Traditional Powele Silat in social studies learning because it is considered relevant to the material on the nation’s cultural diversity in elementary school social studies.